Facile fabrication of antibacterial and antiviral perhydrolase-polydopamine composite coatings - Li-Sheng Wang (Nature Portfolio, 2021)
Abstract In situ generation of antibacterial and antiviral agents by harnessing the catalytic activity of enzymes on surfaces provides an effective eco-friendly approach for disinfection. The perhydrolase (AcT) from Mycobacterium smegmatis catalyzes the perhydrolysis of acetate esters to generate the potent disinfectant, peracetic acid (PAA). In the presence of AcT and its two substrates, propylene glycol diacetate and H2O2, sufficient and continuous PAA is generated over an extended time to kill a wide range of bacteria with the enzyme dissolved in aqueous buffer. For extended self-disinfection, however, active and stable AcT bound onto or incorporated into a surface coating is necessary. In the current study, an active, stable and reusable AcT-based coating was developed by incorporating AcT into a polydopamine (PDA) matrix in a single step, thereby forming a biocatalytic composite onto a variety of surfaces. The resulting AcT-PDA composite coatings on glass, metal and epoxy surfaces yielded up to 7-log reduction of Gram-positive and Gram-negative bacteria when in contact with the biocatalytic coating. This composite coating also possessed potent antiviral activity, and dramatically reduced the infectivity of a SARS-CoV-2 pseudovirus within minutes. The single-step approach enables rapid and facile fabrication of enzyme-based disinfectant composite coatings with high activity and stability, which enables reuse following surface washing. As a result, this enzyme-polymer composite technique may serve as a general strategy for preparing antibacterial and antiviral surfaces for applications in health care and common infrastructure safety, such as in schools, the workplace, transportation, etc.